2021
DOI: 10.1123/jmpb.2021-0024
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Validity of Assessing Low-Income, African American Older Adults’ Physical Activity and Sedentary Behavior Through Ecological Momentary Assessment

Abstract: Ecological momentary assessment (EMA) is a methodological tool that can provide novel insights into the prediction and modeling of physical behavior; however, EMA has not been used to study physical activity (PA) or sedentary behavior (SB) among racial minority older adults. This study aimed to determine the feasibility and validity of an EMA protocol to assess racial minority older adults’ PA and SB. For 8 days, older adults (n = 91; 89% African American; 70% earning <$20,000/year) received six randomly pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…This study capitalizes on the fact that mobile phones have become ubiquitous and easy to use in daily life, even among older adults [ 60 ]. Previous studies have documented that smartphone-based EMA studies of movement-related behavior are feasible, acceptable, and valid among diverse groups of older adults [ 61 , 62 ]. However, this is the first known movement behavior EMA study to intensively assess older adults 10 times per day.…”
Section: Discussionmentioning
confidence: 99%
“…This study capitalizes on the fact that mobile phones have become ubiquitous and easy to use in daily life, even among older adults [ 60 ]. Previous studies have documented that smartphone-based EMA studies of movement-related behavior are feasible, acceptable, and valid among diverse groups of older adults [ 61 , 62 ]. However, this is the first known movement behavior EMA study to intensively assess older adults 10 times per day.…”
Section: Discussionmentioning
confidence: 99%
“…As noted, this can facilitate the pairing of EMA responses with other time-stamped data sources such as accelerometers and allows for the investigation of the temporal sequence of relationships between key constructs. Previous research has established the feasibility and validity of using smartphone-based EMA to assess PA and SB as well as their determinants in diverse populations across their life span [28,[32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…Through a preliminary review of the literature, we found that, in most instances, researchers who have implemented both methods used EMA to assess variables specific to the research question (e.g., momentary affect, episodic anxiety, situational context) and used processed data from accelerometer-based devices to estimate MVPA. Various studies (Bruening et al, 2016;Dunton et al, 2005Dunton et al, , 2012Dunton et al, , 2015Dunton et al, , 2016Ehlers et al, 2016;Knell et al, 2017;Liao et al, 2015Liao et al, , 2020Maher et al, 2018Maher et al, , 2021 have specifically implemented EMA with physical activity-specific survey items (i.e., type, context) and included concurrent accelerometer-based devices. However, the use of physical activity estimates based on accelerometer sensor processing has varied.…”
mentioning
confidence: 99%
“…In some cases, these estimates were used to determine covariates (Dunton et al, 2015) or dependent variables (Liao et al, 2015), or for assessing weartime feasibility (Ehlers et al, 2016). A primary use in a number of studies (Bruening et al, 2016;Dunton et al, 2005Dunton et al, , 2012Dunton et al, , 2016Knell et al, 2017;Maher et al, 2018Maher et al, , 2021 was to validate EMA reports of physical activity/exercise. That is, researchers isolated acceleration data pertaining to 5, 10, 15, or 30 min preceding each EMA prompt, which asked respondents to report activities that were being performed at the time of the prompt, and processed these data to estimate average counts per minute, MVPA, or step bouts across the target time frame.…”
mentioning
confidence: 99%